Privacy and app use in Australian primary schools: insights into school-based Internet governance. Issue 1 (February 2019) - Rennie, Ellie; Schmieder, Kathrin; Thomas, Julian; Howard, Sarah K; Ma, Jun; Yang, Jack
This article identifies the apps that are most frequently used in 148 Australian primary schools and categorises them by their stated treatment of identifiable information. Rather than providing a legal analysis, we use this as evidence of Internet governance insofar as it illuminates the influence of the education sector on the behaviour of technology companies. Teachers' decision-making in the selection of apps is far from uniform, making individual guardian consent an inadequate approach to the protection of children. The failure of consent leads to other legal and self-regulatory approaches through which the state and technology companies together recreate the school's role as administrator over the conduct and formation of future digital citizens.